Circulation‐Driven Larval Dispersal Patterns Are Sufficient to Set the Location of Numerous Coastal Biogeographic Boundaries - William G. Lush; James M. Pringle; James E. Byers (Journal of Biogeography, 2026)
Aim This study explores how and where contemporary coastal biogeographic structure is set by patterns of circulation‐driven meroplanktonic larval dispersal. Location Along the continental shelf globally between 80° N and 56° S. Taxon No taxon is discussed directly. This work uses a modelling approach to simulate dispersal and eventual abundance patterns of meroplanktonic organisms that are sedentary as adults, with pelagic larval durations between 3 and 45 days. Methods Lagrangian particle tracking was used to simulate larval dispersal using passively‐advected near‐surface particles in velocity fields from the Mercator Ocean 1/12° global physical model. Connectivity from these dispersal simulations was used to drive dispersal in a neutral population model with many identically‐dispersing and competitively equal model ‘species.’ Locations where many model species range edges clustered were compared against observed biogeographic boundaries from the Marine Ecoregions of the World (MEOW) framework. Results Model boundaries predicted MEOW boundaries better than random chance for most seasonal breakdowns from 15‐ to 45‐day pelagic larval durations (PLDs); shorter PLDs could not be shown to be meaningfully different from random chance. When results were shown to be significantly different from random chance, circulation‐driven model boundaries predicted between 25% and 40% of MEOW boundaries (depending on season and PLD). Main Conclusions Circulation‐driven larval dispersal is sufficient to set the location of many contemporary biogeographic boundaries for organisms with PLDs longer than 15 days.